DRAIN AMYLASE LEVELS MAY INDICATE GASTROJEJUNOSTOMY LEAKS AFTER ROUX-EN-Y GASTRIC BYPASS - RIBEIRO,Igor Braga (2018)
ABSTRACT BACKGROUND: Although the incidence of leaks after Roux-en-Y gastric bypass (RYGB) significantly decreased over time, their detection still remains challenging. OBJECTIVE: This study aimed to determine the usefulness of drain amylase levels to detect leaks after RYGB. METHODS: This is a population-based study which enrolled 170 individuals who underwent RYGB. Drain amylase levels were determined on the first and fourth postoperative days. Two thresholds were evaluated: three times higher than the serum levels (parameter I) and higher than 250 IU/L (parameter II). The main outcomes evaluated were perioperative morbidity, the occurrence of leaks, 30-day readmissions and reoperations, hospital stay, and mortality. RESULTS: Considering the parameter I, high drain amylase levels were significantly associated with leaks (12.5% vs 0; P<0.00001). Considering the parameter II, high drain amylase levels were significantly associated with longer hospital stay (8±5.7 vs 4.5±1.3 days; P=0.00032), 30-day reoperations (50% vs 3%; P=0.000285), and leaks (50% vs 0; P<0.00001). The parameter I presented a sensitivity of 100% and specificity of 95.9%, whereas the parameter II presented a sensitivity of 100% and a specificity of 99.4%. CONCLUSION: The determination of drain amylase levels after RYGB was a significant indicator of leaks, hospital stay, and 30-day reoperations. This finding reinforces the importance of abdominal drainage in the RYGB within this context.